Contagion Effects in Financial Markets: Influence of Green Finance and Energy Sectors During Global Crises - Khemakhem, Imen; Gallas, Salma; Aissi, Amen (International Journal of Energy Economics and Policy, 2025)
This study investigates the dynamic volatility interconnectedness between green bonds, renewable energy, fossil fuels, and the global sustainability index from September 01, 2014, to May 31, 2023. An overall volatility connectedness index of 46.77% is found through the use of an enhanced joint connectedness method in conjunction with a time-varying parameter vector autoregression (TVP-VAR) model. Marked increases in connectedness are observed through pivotal global events, like the oil shale shock, Coronavirus outbreak, and geopolitical turmoil following the Ukraine invasion, indicating contagion effects across the markets. Key findings reveal that the Green Bond Index, WTI Crude Oil, and Natural Gas indices from S&P GSCI are the leading net transmitters of volatility, while the DJ Sustainability World Index, Renewable Energy, and S&P GSCI Brent Crude primarily act as net receivers. Results offer valuable insights for environmentally focused investors, enabling them to mitigate risk through diversified portfolios of sustainable assets. Policymakers can also leverage these findings to recognize the impact of global events on financial stability and devise strategies that promote resilience and green finance adoption.